Accountability For the Implementation of the Buy The Service Scheme in Mass Transportation - martha marsikun, ipoeng; Wahyuningsih, Eri; Faozanudin, Muslih; Kurniasih, Denok (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
program initiated by the Ministry of Transportation of the Republic of Indonesia with a service purchase scheme from operators both from private companies and state/regional owned companies with a work contract system for a predetermined time. The Ministry of Transportation provides requirements for operators to meet minimum service standards and standard operational procedures in providing these services. The accountability and sustainability of this program is still a serious consideration. The Buy The Service scheme was implemented in 2020 in 5 old cities, namely Denpasar, Palembang, Surakarta, Medan and Jogjakarta and in 2021 followed in 5 new cities, including Banyumas, Surabaya, Bandung, Banjarmasin and Makasar. Accountability is a very important aspect from the procurement process to program implementation because it uses the State Revenue and Expenditure Budget (APBN). With large initial capital, this program is a tough challenge for BTS service operators. Purchases of vehicles, IoT (Internet of things) equipment, bicycle racks, workshop and office equipment and other facilities that have been prepared by Operators and Regional Governments will certainly be in vain and detrimental to many parties if the continuation of this program is stopped. It is hoped that commitment from all stakeholders can collaborate with each other in the ongoing process of this buy the service program.